Educating moral sensitivity in business: An experimental study to evaluate the effectiveness of a serious moral game. (March 2022) - Tanner, Carmen; Schmocker, David; Katsarov, Johannes; Christen, Markus
Abstract: Serious games have emerged as a promising new form of education and training. Even though the benefits of serious games for education are undisputed, there is still a further need for research on the efficacy of such games. The main goal of our research is to examine the effectiveness of a serious moral game— uFin: The Challenge— that was designed to promote moral sensitivity in business, a precondition of ethical decision-making and behavior and a core moral competency of moral intelligence. A second goal is to examine the role of metacognitive prompting and prosocial nudging in influencing learning effectiveness. Participants ( N  = 345) took part in an experimental game-based intervention study and completed a pre- and post-test questionnaire assessing moral sensitivity. The analyses of both questionnaire and game data suggest that merely playing this game is effective in promoting moral sensitivity. Neither self-reflection nor exposure to prosocial nudges, however, were determined to be factors that improve learning effectiveness. In contrast, those interventions even decreased the learning outcome in some cases. Overall, findings demonstrate the potential for game-based learning in the moral domain. An important avenue for future research is to examine others ways of increasing the effectiveness of the game. Highlights: Serious moral games pose an appealing strategy for the training of moral competences. Moral sensitivity can be fostered through serious games. Contrary to previous research, self-reflection did not increase moral sensitivity. Exposure to prosocial nudges in a serious game did not promote moral sensitivity.